2018
DOI: 10.1101/330084
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

mitoNEET Regulates Mitochondrial Iron Homeostasis Interacting with Transferrin Receptor

Abstract: 33Iron is an essential trace element for regulation of redox and mitochondrial function, 34 and then mitochondrial iron content is tightly regulated in mammals. We focused on a 35 novel protein localized at the outer mitochondrial membrane. Immunoelectron 36 microscopy revealed transferrin receptor (TfR) displayed an intimate relationship with 37 the mitochondria, and mass spectrometry analysis also revealed mitoNEET interacted 38 with TfR in vitro. Moreover, mitoNEET was endogenously coprecipitated with TfR i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 41 publications
0
3
0
Order By: Relevance
“…In this study, we demonstrated that inhibiting mitoNEET, a mitochondrial iron regulator, has a protective effect against inflammatory responses during sepsis. MitoNEET, a mitochondrial protein, plays a key role in energy metabolism, iron regulation, and production of ROS by mitochondria [ 19 , 43 ]. Our data show that inflammatory stimuli, such as LPS, which induce mitochondrial oxidative damage, trigger production of mitoNEET mRNA and protein in various animal models of and in BMDMs (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…In this study, we demonstrated that inhibiting mitoNEET, a mitochondrial iron regulator, has a protective effect against inflammatory responses during sepsis. MitoNEET, a mitochondrial protein, plays a key role in energy metabolism, iron regulation, and production of ROS by mitochondria [ 19 , 43 ]. Our data show that inflammatory stimuli, such as LPS, which induce mitochondrial oxidative damage, trigger production of mitoNEET mRNA and protein in various animal models of and in BMDMs (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies revealed that different cell types with reduced CISD2 or CISD1 expression accumulate high levels of iron in their mitochondria and display enhanced expression of TfR and ferritin [54,58,63]. This process is also accompanied by the activation of apoptosis, autophagy, and ferroptosis [16,33,50,54,57,58,64,65].…”
Section: Discussionmentioning
confidence: 99%
“…Downregulating any one of the NEET proteins, including MiNT, leads to increased accumulation of mitochondrial labile iron (mLI) and mitochondrial reactive oxygen species (mROS), as well as to disruptions in mitochondrial function and morphology ( 12 , 14 , 17 ). Mitochondrial iron and ROS accumulation were shown to affect mitochondrial respiratory capacity ( 12 , 18 26 ). Since mitochondria are considered to play a central role in bioenergetics, metabolism, and other cellular pathways ( 27 ), mitochondria morphodynamics are tightly linked to the overall bioenergetic function of cells ( 28 ).…”
mentioning
confidence: 99%